Caregiver knowledge of hypoglycemia and hyperglycemia management in children and adolescents with type 1 diabetes - Matthew Feldman; Grace PS Kwong; Josephine Ho (Diabetes Epidemiology and Management)
Objective: To determine the current knowledge of the assessment and management of acute diabetes-related complications including severe hypoglycemia and diabetic ketoacidosis (DKA) among caregivers of patients with type 1 diabetes (T1D). Methods: A cross-sectional survey was completed at a tertiary care pediatric hospital diabetes clinic from November 2021 to July 2022. Data was analyzed from all completed survey responses and included both Likert and evaluation-style questions. Results: A total of 152 surveys were collected and 96 were included in the analysis. Caregiver knowledge on management of hypoglycemia was significantly better than their knowledge on hyperglycemia management (median score 100 % vs 60 %, p-value <0.001). There was no difference in caregiver knowledge around assessment of hypoglycemia or hyperglycemia (median score 88.9 % vs 88.9 %, p-value 0.909). There was no significant difference in overall knowledge as determined by percentage of questions correct between those on different blood glucose monitors (p-value 0.184) or whether the parent/caregiver or the patient were primarily responsible for T1D management (p-value 0.964). There was no difference in total score by management type when adjusted using the Bonferroni method. There was also no significant interaction by level of caregiver involvement. Conclusions: Caregiver knowledge of management of hypoglycemia was significantly better than their knowledge of management of hyperglycemia in pediatric T1D. Blood glucose monitoring or T1D management type was not found to be associated with any differences in caregiver knowledge in the assessment or management of hypoglycemia or hyperglycemia.